Selective Isomorphism of Silicon, Aluminium and Titanium in the Extra-Large Pore Zeolite-Like Germanate IPC-3 - Oleksiy V. Shvets; Natalia V. Kasian; Volodymyr G. Ilyin (Adsorption Science & Technology)
Zeolite IPC-3 — which is isostructural with the extra-large pore germanate zeolite ASU-16 — and its Si, Al and Ti forms were synthesized using 1,6-diaminohexane as the template. It was established that the Si atoms occupy the tetrahedral positions in the IPC-3 framework, the Al atoms occupy the octahedral or tetrahedral positions and the Ti atoms the octahedral positions. The germanate zeolite IPC-3 and Si-, Al- and Ti-IPC-3 are stable up to 200–300°C. Despite the presence of the template, which stabilizes the framework of IPC-3, the adsorption capacities of samples previously degassed at 200°C were up to 0.13 cm 3 /g.